Modulating factors of reproductive seasonality in ungulates - Urviola García, Adriana Pilar (2017)
The aim of the following review is to describe the seasonal reproductive behavior in male and female ungulates, and identify the determinants of reproductive synchrony. Intrinsic and extrinsic factors that influence the reproductive seasonality of ungulates analyzed. Intrinsic factors are related to the same individual such as genotypic and phenotypic characteristics, and implies that the reproductive aspects can not be extrapolated between species and breeds, and are modified by the action of external factors such as photoperiod, availability of food, temperature, latitude, among others. Among these factors are identified primarily photoperiod and food availability. The photoperiod and food availability are the main signals that determine melatonin levels, and this modulates the reproductive function. Photoperiod is related to the intensity of light and darkness that animals are exposed to and is expressed in the production of melatonin. They describe that the mechanisms of action of this hormone in the central nervous system (CNS) to exert their effects on reproductive function. The nutritional factor is also an important regulator of reproductive seasonality, which could be stimulating the hypothalamic pituitary gland, causing a direct effect on LH release. Then endocrine basis regulating reproductive seasonality in species belonging to the subclass Eutheria, families Bovidae, Camelidae, Equidae and Suidae, wild and domestic, stating differences between them are discussed.